2015
DOI: 10.5999/aps.2015.42.6.741
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Take-Back Operations in Breast Reconstruction with Free Lower Abdominal Flaps

Abstract: BackgroundMicrovascular complications after free-flap breast reconstructions are potentially devastating problems that can increase patient morbidity and lead to flap loss. To date, no comprehensive study has examined the rates of salvage and the methods of microvascular revision in breast reconstruction. We reviewed the treatment of microvascular complications of free-flap breast reconstruction procedures over a seven-year period.MethodsA retrospective review of all patients who underwent microvascular breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…We noted a flap salvage rate of 33%, with earlier identification of flap compromise being associated with higher rates of flap salvage. 20,22,80,85,93,102,103 The incidence of hematomas requiring operative intervention was also comparable to other studies: chest hematomas occurred at a rate of 1.86% and abdominal hematomas at a rate of 0.62%. 84,91,94,96,104 Protocol Success There is no single "key" element of our protocol which is the source of its success.…”
Section: Unplanned Reoperations and Free Flap Failuresupporting
confidence: 86%
See 1 more Smart Citation
“…We noted a flap salvage rate of 33%, with earlier identification of flap compromise being associated with higher rates of flap salvage. 20,22,80,85,93,102,103 The incidence of hematomas requiring operative intervention was also comparable to other studies: chest hematomas occurred at a rate of 1.86% and abdominal hematomas at a rate of 0.62%. 84,91,94,96,104 Protocol Success There is no single "key" element of our protocol which is the source of its success.…”
Section: Unplanned Reoperations and Free Flap Failuresupporting
confidence: 86%
“…20,[79][80][81][82][83] In large-scale studies, rates of postoperative vascular complications requiring unplanned reoperation vary significantly from 1.8 to 9.1%. 78,[84][85][86][87][88][89][90][91][92][93][94] Experienced microvascular surgeons report free flap failure rates between 0.7 and 2.9%. 84,[86][87][88][89][91][92][93][94][95][96][97][98][99][100][101] The present study demonstrated similar incidences of 1.86 and 0.69%, respectively.…”
Section: Unplanned Reoperations and Free Flap Failurementioning
confidence: 99%
“…Flap take-backs to theatre due to venous or arterial insufficiency were recorded in 14.0% of patients (42/300) and were successful in 55.8% of patients. This confirms lower rates of successful flap salvage in TMG flaps compared to DIEP flaps [24]. A potential reduction of fat necrosis in PAP flaps due to a more centralized perforator in the skin island is still discussed but exact perfusion studies to quantify the blood flow through the individual angiosome have not been conducted so far [22].…”
Section: Discussionmentioning
confidence: 83%
“…Even in the event that a failing flap is salvaged, we feel and have found in our experience that there is a critical amount of ischemia and reperfusion injury resulting in significant fat necrosis and unacceptable aesthetic and functional results, thus raising the question of the value of delayed flap salvage past the 23-hour window. 21 It is due to this fact that we believe routine monitoring is not necessary after 23 hours.…”
Section: Discussionmentioning
confidence: 99%